Investigation of the impact of a standard lightning impulse on the structure of an 11/0.415 kV distribution transformer - Murthy, Avinash Srikanta; Azis, Norhafiz; Jasni, Jasronita; Othman, Mohd Lutfi; Mohd Yousof, Mohd Fairouz; Martin, Daniel; Talib, Mohd Aizam (Elsevier, 2022)
In this paper a model has been proposed to investigate the effect of Standard Lightning Impulses at voltages below the Basic Insulation Level (BIL) on winding geometry, based on the extraction of resistances, inductances, capacitances and conductance using Finite Element Method (FEM) and the resultant structural movement. The winding and insulation in a transformer can be subjected to overvoltage surges i.e. lightning strikes and switching events. If the frequency component of the incoming transient surges matches the resonance frequency zone of the transformer windings, the amplification and attenuation of the overvoltages along the windings may result in abnormal voltage stress on the conductors of the winding. Hence, the monitoring of electromagnetic forces and the resultant mechanical stresses are of paramount importance in the minimization of the occurrence of mechanical failure in transformers. The Standard Lightning Impulse (SLI) was induced at the outermost layer of the High Voltage (HV) winding of the 11/0.415 kV transformer and resultant electromagnetic forces acting in axial and radial directions were computed. The computed directional forces were in turn induced to the winding structure to observe the structural behavior. The FEM model was tested using an SLI with a voltage, 35 kV, below the BIL of this class of transformer. The modeling showed that the axial and radial forces impinge a mechanical stress in the outer column supports of the winding structure. This model will allow the investigation of buckling within windings at elevated voltages above the BIL.